2019
DOI: 10.3390/su11030682
|View full text |Cite
|
Sign up to set email alerts
|

Female CEOs and Corporate Innovation Behaviors—Research on the Regulating Effect of Gender Culture

Abstract: With the increasing number of female senior executives, the relationship between female senior executives and corporate innovation behaviors has attracted widespread attention, but few works have studied the influences of female CEOs on innovation behaviors and their mechanisms. This paper studies the relationship between CEO's gender and the selection of corporate innovation behaviors, as well as the regulating effect of gender culture on the relationship between them. It was discovered in the studies that (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…However, the research associating types of innovation with firm performance is limited. Further, extant research focuses more on understanding the effects of radical or incremental innovation of new products when correlating the effect of technological innovation on the firms' performance [19][20][21][22][23][24][25][26]. This study identified that the continuity of incremental innovation, scaling, is important to improving the firms' sustainable performance based on the findings from the NAND flash industry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the research associating types of innovation with firm performance is limited. Further, extant research focuses more on understanding the effects of radical or incremental innovation of new products when correlating the effect of technological innovation on the firms' performance [19][20][21][22][23][24][25][26]. This study identified that the continuity of incremental innovation, scaling, is important to improving the firms' sustainable performance based on the findings from the NAND flash industry.…”
Section: Discussionmentioning
confidence: 99%
“…Then the dominant architecture moves to the left again for continuous incremental innovation until new architecture is introduced to reframe the innovation activities in the industry. In terms of benefits from innovation, extant research has focused more on incremental and radical innovation types, including new product development [19][20][21][22][23][24][25][26]. The research focus on incremental innovation might be due to the fact that incremental innovation is used extensively and is easily attempted in the industry.…”
Section: Radical Innovation Development Of Non-silicon Based Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Women will also develop themselves in the process of participating in sustainable development. After that, family and marriage patterns also underwent major changes, and this change was also gradually strengthened, thus forming the male-dominated gender culture [9]. Under this gender culture, people gradually formed their understandings and even prejudices against male and female.…”
Section: Female and Sustainable Developmentmentioning
confidence: 99%
“…However, as we see, with women's education levels going up and their years of working and working experience increasing, their positions and levels have not improved accordingly. Only marriage patterns also underwent major changes, and this change was also gradually strengthened, thus forming the male-dominated gender culture [9].…”
Section: Introductionmentioning
confidence: 99%